Mesoporous silica nanoparticles functionalized with folic acid for targeted release Cis-Pt to glioblastoma cells - Ortiz-Islas Emma (De Gruyter, 2021)
This work reports the preparation, characterization, and a drug release study of mesoporous silica nanoparticles (MNPSiO2) functionalized with folic acid (FA) and loaded with Cis-Pt as a targeted release system to kill glioblastoma cancer cells. The MNPSiO2 were synthesized by the Stöber method using hexadecyltrimethylammonium bromide as the templating agent, which was finally removed by calcination at 550°C. The folic acid was chemically anchored to the silica nanoparticles surface by a carbodiimide reaction. Several physicochemical techniques were used for the MNPSiO2 characterization, and a triplicate in vitro Cis-Pt release test was carried out. The release Cis-Pt experimental values were fitted to different theoretical models to find the Cis-Pt release mechanism. The cytotoxicity evaluation of the MNPSiO2 was performed using LN 18 cells (human GBM cells). Homogeneous and well-defined nanoparticles with well-distributed and homogeneous porosity were obtained. The spectroscopic results show the proper functionalization of the mesoporous nanoparticles; besides, MNPSiO2 showed high surface area and large pore size. High correlation coefficients were obtained. Though the best fitted was the Korsmeyer-Peppas kinetic model, the Higuchi model adjusted better to the results obtained for our system. The MNPSiO2-FA were highly biocompatible, and they increased the cytotoxic effect of Cis-Pt loaded in them.